An optimization design method for aerodynamic configuration of high aspect ratio wing. Issue 1 (February 2021) - Zong, Ning; Sun, Jing; Dong, Meijuan
Abstract: The aerodynamic shape optimization design of the aircraft is to combine the aerodynamic performance analysis of the aircraft with the optimization method, by constantly changing the design shape of the aircraft, its aerodynamic performance is improved to achieve optimal aerodynamic performance under certain constraints. Aircraft aerodynamic shape optimization is a comprehensive design platform that integrates geometric parameterization, moving grid, CFD calculation and optimization algorithms. With the development of computational fluid dynamics (CFD) and the maturity of calculation methods, the role of aerodynamic shape optimization in modern aircraft design becomes more and more important. To this end, an aerodynamic shape optimization design platform based on non-uniform rational B-spline (NURBS) was established. In the optimization process, a mesh deformation method based on radial basis functions is used, and an arbitrary Lagrangian Eulerian method (ALE) is used to describe the unsteady process of the wing. The optimization analysis of the large aspect ratio wing under subsonic conditions has certain reference value for the deformation problem in the aerodynamic shape optimization design.